Leafy vegetables in Chapai Nawabganj district of Bangladesh focusing on medicinal value (Bangladesh Journal of Plant Taxonomy, 2020)
Leafy vegetables in Chapai Nawabganj district of Bangladesh was studied from January to December 2019. A total of 111 species belonging to 59 genera under 30 families were recorded, out of which, 52.25% species were wild and 46.84% species were cultivated in this study. Status of occurrence has been recorded for proper conservation management and sustainable utilization of the taxa resulting in 81.98% to be common, 17.11% as rare and 0.90% are found as vulnerable in the study area. A total of 93 medicinal plants have been documented with their uses for the cure of more than 53 diseases. The study showed that the people of Chapai Nawabganj district use leafy vegetables to treat their diseases. Therefore, the documented leafy vegetables should be further investigated for their efficacy and safety to be integrated into conventional medicine. Further more these leafy vegetables need to be conserved for their sustainable utilization.Bangladesh J. Plant Taxon. 27(2): 359-375, 2020 (December)